AN ANALYSIS OF LIGHT-KINETIC SCULPTURE FROM THE MIDDLE OF THE 20TH CENTURY. CASE STUDY – NICOLAS SCHÖFFER - NAE, OANA MARIA (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică)
The transition from the consciousness of matter to that of light, together with the discoveries of science at the beginning of the 20th century, can be noted by the rapid development of the light space, understood as the space conquered by screens or projections. The screen replaces the window, lending it its importance in terms of lighting, but also the source of information, the relationship of man with the outside of the environment in which he lives. In this idea, the avant-garde artists, but especially those who followed after the Second World War, will create real light shows from their work. One such example is the artist Nicolas Schöffer, whom we will analyze from the perspective of his theoretical ideas, his experiments and his works of art in which technology becomes an important support for the artistic idea, thus becoming a paradigm for other European artists of the time.